KONSTRUKSI PLASMID PRHA SEBAGAI PEMBAWA GEN ARAA PENYANDI ENZIM L-ARABINOSA ISOMERASE DARI Thermotoga thermarum - M Masfuroh; Anto Budiharjo; Hermin Pancasakti Kusumaningrum (Jurnal Akademika Biologi, 2017)
D-tagatosa as natural low-calorie sweeterners is likely to be a sugar substitute for diabetics type II. D-tagatosa sweetness levels is by 92% the sweetness of sucrose, but only 38% of calories of sucrose. This study aimed to obtain a recombinant plasmid construction pRHA::araA. Results subcloning was then used in biotransformation processes produce D-tagatosa. Propagation vector soure pRHA   was done with the cloning procedure in E. coli TOP’10. The process  used the vector source cut with enzyme NcoI and XhoI and producing pRHA vectore for gene insertion araA. AraA gene amplification was done using Polymerase Chain Reaction (PCR)  with  primers of AITth-For and AITth-Rev. Ligation was done using T4 ligase enzyme and transformed in E. coli TOP’10 by heat-shock methods. E. coli was grown in LB medium Agar with ampicillin concentration of 100 mg/ml. Selection was made on a liquid LB and LB Agar with ampicillin concentration range of 100-200 mg/ml. Based on the result of electrophoresis visualization of the pRHA::araA recombinant plasmid isolation were negative. Keyword:  L-arabinosa isomerase, araA, D-tagatosa, T. thermarum, E. coli